Peran Guru PPKn dalam Membentuk Pemahaman Hak dan Kewajiban Warga Negara Melalui Metode Pembelajaran Aktif pada Siswa Kelas IV SDN Gunung Gatep Lombok Tengah - Tresna Bintang Kusuma Hakyky; Ati Sukmawati; Syudirman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the role of Civic Education (PPKn) teachers in shaping students’ understanding of citizens’ rights and obligations through active learning methods. This research uses a qualitative descriptive approach conducted at SDN Gunung Gatep, Central Lombok. The subjects consisted of PPKn teachers, 36 fourth-grade students, and the school principal. Data were collected through observation, interviews, and documentation. The findings show that the learning process is still dominated by teacher-centered methods such as lectures and question-answer sessions. Only 10 out of 36 students (±28%) were able to provide concrete examples of rights and obligations in daily life. Interviews revealed that students tend to memorize definitions without understanding their practical application. Teachers have implemented active learning methods such as discussions, group work, and role play, but student engagement remains uneven. The study concludes that although active learning contributes positively, its implementation has not been optimal due to limited time, varied student abilities, and low participation. Therefore, more adaptive teaching strategies and authentic evaluation are needed to improve students’ understanding.